Observations of Manaus urban plume evolution and interaction with biogenic emissions in GoAmazon 2014/5. (October 2018) - Cirino, Glauber; Brito, Joel; Barbosa, Henrique M.J.; Rizzo, Luciana V.; Tunved, Peter; de Sá, Suzane S.; Jimenez, Jose L.; Palm, Brett B.; Carbone, Samara; Lavric, Jost V.; Souza, Rodrigo A.F.; Wolff, Stefan; et al.
Abstract: As part of the Observations and Modeling of the Green Ocean Amazon (GoAmazon 2014/5) Experiment, detailed aerosol and trace gas measurements were conducted near Manaus, a metropolis located in the central Amazon Basin. Measurements of aerosol particles and trace gases were done downwind Manaus at the sites T2 (Tiwa Hotel) and T3 (Manacapuru), at a distance of 8 and 70 km from Manaus, respectively. Based on in-plume measurements closer to Manaus (site T2), the chemical signatures of city emissions were used to improve the interpretation of pollutant levels at the T3 site. We derived chemical and physical properties for the city's atmospheric emission ensemble, taking into account only air masses impacted by the Manaus plume at both sites, during the wet and dry season Intensive Operating Periods (IOPs). At T2, average concentrations of aerosol number (CN), CO and SO2 were 5500 cm −3 (between 10 and 490 nm), 145 ppb and 0.60 ppb, respectively, with a typical ratio ΔCN/ΔCO of 60–130 particles cm −3 ppb −1 . The aerosol scattering (at RH < 60%) and absorption at 637 nm at T2 ranged from 10 to 50 M m −1 and 5–10 M m −1, respectively, leading to a mean single scattering albedo (SSA) of 0.70. In addition to identifying periods dominated by Manaus emissions at both T2 and T3, the plume transport between the two sampling sites was studied using back trajectory calculations. Results show that the presence of the Manaus plume at site T3 was important mainly during the daytime and at the end of the afternoons. During time periods directly impacted by Manaus emissions, an average aerosol number concentration of 3200 cm −3 was measured at T3. Analysis of plume evolution between T2 and T3 indicates a transport time of 4–5 h. Changes of submicron organic and sulfate aerosols ratios relative to CO (ΔOA/ΔCO and ΔSO4 /ΔCO, respectively) indicate significant production of secondary organic aerosol (SOA), corresponding to a 40% mass increase in OA and a 30% in SO4 mass concentration. Similarly, during air mass arrival at T3 the SSA increased to 0.83 from 0.70 at T2, mainly associated with an increase in organic aerosol concentration. Aerosol particle size distributions show a strong decrease in the Aitken nuclei mode (10–100 nm) during the transport from T2 to T3, in particular above 30 nm, as a result of efficient coagulation processes into larger particles. A decrease of 30% in the particle number concentration and an increase of about 50 nm in geometric mean diameter were observed from T2 to T3 sites. The study of the evolution of aerosol properties downwind of the city of Manaus improves our understanding of how coupling of anthropogenic and biogenic sources may be impacting the sensitive Amazonian atmosphere. Graphical abstract: Image 1 Highlights: Manaus emissions significantly impacts Amazonian aerosols properties. Organic aerosols increase 40% in mass downwind of Manaus, attributed to secondary formation. Sulfate aerosols increase 30% in mass downwind of Manaus, attributed to SO2 oxidation. Aerosol mean diameter increases about 60 nm during plume evolution, in the dry season.